2012
DOI: 10.1016/j.neuron.2012.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Critical Roles for Anterior Insula and Dorsal Striatum in Punishment-Based Avoidance Learning

Abstract: The division of human learning systems into reward and punishment opponent modules is still a debated issue. While the implication of ventral prefrontostriatal circuits in reward-based learning is well established, the neural underpinnings of punishment-based learning remain unclear. To elucidate the causal implication of brain regions that were related to punishment learning in a previous functional neuroimaging study, we tested the effects of brain damage on behavioral performance, using the same task contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
201
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(234 citation statements)
references
References 52 publications
(77 reference statements)
29
201
1
Order By: Relevance
“…Therefore, additional information on costs is required to perform these decision-making computations. Representations of costs indeed have been observed in areas such as the anterior cingulate cortex (50)(51)(52)(53)(54), insular cortex (55,56), and basolateral amygdala (49,57), all of which provide glutamatergic inputs that converge on striatal projection neurons. Therefore, a more integrative valuation system could arise from the downstream combination of benefit information from the dopamine-associated cached values and cost information from other neural sources.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, additional information on costs is required to perform these decision-making computations. Representations of costs indeed have been observed in areas such as the anterior cingulate cortex (50)(51)(52)(53)(54), insular cortex (55,56), and basolateral amygdala (49,57), all of which provide glutamatergic inputs that converge on striatal projection neurons. Therefore, a more integrative valuation system could arise from the downstream combination of benefit information from the dopamine-associated cached values and cost information from other neural sources.…”
Section: Discussionmentioning
confidence: 98%
“…Single case analysis (Table S6) indicated that these patients were most disrupted on the two distortions, but also showed that some attenuation was clearly present in the insula cases with no striatal involvement. Larger studies are needed to resolve the functional dissociations between insula and (dorsal) striatum (62). It could be reasoned that striatally mediated effects should also interfere with win processing and the personal choice manipulation (63,64), which was not the case.…”
Section: Discussionmentioning
confidence: 99%
“…Taking another perspective to interpret the Treatment × Trait interaction, we examined the relationship between trait measurement and BU Undes for OT and PL group, respectively. Under PL, there was a significant correlation between trait scores and BU Undes because individuals To examine OT effects on the dynamic learning processes of desirable and undesirable feedback, for each participant we calculated the learning rate [i.e., the strength of association between the estimation error (prediction error) and the subsequent updates, SI Appendix, SI Methods], which has been suggested as a computational principle that underlies the observed biased belief formation by pointing to estimation errors as a learning signal (45) and reflects the dynamic learning processes of prediction errors (46). The Treatment × Feedback ANOVA of collapsed data from studies 1-3 revealed a significant main effect of Feedback as participants learned to a greater degree from estimation errors in the desirable (than undesirable) trials [F(1,306) = 246.482, P < 0.001].…”
Section: Distinct Ot Effects In Individuals With High and Low Depressmentioning
confidence: 99%